Optimizing Hyaluronic Acid: A Comprehensive Review of Rheological Insights for Clinical Practice (Global Journal of Medical Research, 2023)
The aging process of the face is characterized by transformations in the skin bone and adipose tissue As the understanding of these changes has expanded so too has the range of available filler products in the market To maximize the effectiveness of hyaluronic acid it is crucial to have a comprehensive understanding of its rheological properties The numerous commercially available brands of hyaluronic acid differ in several aspects such as the purity of their raw materials methods of manufacturing concentration of hyaluronic acid presence and level of cross-linking and ability to provide volume and withstand degradation Aiming at the most assertive use of this product features as viscosity complex modulus G elastic modulus G tan d cross-linking concentration and swelling factor must be addressed correlating them with their expected clinical effects
Keywords: cohesiveness; extrusion force; hyaluronic acid; rheology; skin quality improvement; swelling degree